2018
DOI: 10.1590/1678-98652018000600007
|View full text |Cite
|
Sign up to set email alerts
|

Healthy eating through the eyes of adolescents: A qualitative analysis of messages from the Dietary Guidelines for the Brazilian Population

Abstract: Objective To evaluate the interpretation by adolescents of messages contained in the Dietary Guidelines for the Brazilian Population. Methods Qualitative study of adolescents distributed across “conversation circles”. Each group received messages about healthy eating from the Dietary Guidelines and was instructed to develop materials containing their own interpretation thereof, using appealing wording and format. Content analysis was then used to evaluate these materials. Results Presentation of the produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…In this case, both pasteurized milk, ultra-pasteurized milk (long-life/UHT), and dehydrated milk (powder) are classified in the same group—either as in natura or as minimally processed food [ 7 , 48 ]. The study by Chagas, Botelho, and Toral [ 49 ] showed that participants classified cooked carrot and broccoli-based food as “semi-industrialized” food because they had undergone “minimal processing”. Likewise, these respondents attributed ultra-processed food definitions as industrialized and mega-industrialized food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, both pasteurized milk, ultra-pasteurized milk (long-life/UHT), and dehydrated milk (powder) are classified in the same group—either as in natura or as minimally processed food [ 7 , 48 ]. The study by Chagas, Botelho, and Toral [ 49 ] showed that participants classified cooked carrot and broccoli-based food as “semi-industrialized” food because they had undergone “minimal processing”. Likewise, these respondents attributed ultra-processed food definitions as industrialized and mega-industrialized food.…”
Section: Discussionmentioning
confidence: 99%
“…According to the food classification mentioned above, the authors obtained similar results regarding the number of correct answers [ 7 ]. The study of Chagas, Botelho, and Toral [ 49 ] qualitatively evaluate adolescents’ understanding of FGBP messages (n = 141). At the same time, research by Figueiredo [ 9 ] aimed to identify the knowledge of professionals (n = 25) in the health area and whether these professionals applied the FGBP in their work.…”
Section: Discussionmentioning
confidence: 99%
“…Deste modo, o objetivo da classificação NOVA é justamente definir de modo específico os diferentes tipos de processamento de alimentos de acordo com a extensão e propósito [3]. Diversos trabalhos vêm demonstrando que tanto adolescentes como adultos ainda apresentam dificuldade em classificar os alimentos de acordo com o processamento [4][5][6]21]. Atribuise esta dificuldade ao fato que para identificar a qual categoria pertence um alimento é preciso considerar além do seu nome e descrição curta, a sua lista de ingredientes e associá-los aos conceitos da classificação NOVA [24].…”
Section: (A1) Pipoca Por Exemplo Feita Em Casa Eu Achava Que Era Alim...unclassified
“…Embora nas respostas anteriores os adolescentes apresentaram certo conhecimento a respeito do saudável e não saudável associado, respectivamente, aos alimentos in natura e ultraprocessados, ainda parecem não ter certeza de que, de fato, alguns alimentos não devem ser consumidos. O estudo de Chagas, et al [6] demonstrou também que adolescentes adotaram uma prática mutuamente excludente entre os alimentos que devem ou não devem ser consumidos.…”
Section: (A3) Alimentos Preparados Em Casa Mais Naturais Vão Benefici...unclassified
See 1 more Smart Citation